The diversity of aroids (Araceae) in Bogor Botanic Gardens, Indonesia: Collection, conservation and utilization - YUZAMMI YUZAMMI (Society for Indonesian Biodiversity, 2018)
Yuzammi. 2018. The diversity of aroids (Araceae) in Bogor Botanic Gardens, Indonesia: Collection, conservation and utilization. Biodiversitas 19: 140-152. Bogor Botanic Gardens is an ex-situ conservation centre, covering an area of 87 ha, with 12,376 plant specimens, collected from Indonesia and other tropical countries throughout the world. One of the richest collections in the Gardens comprises members of the aroid family (Araceae). The aroids are planted in several garden beds as well as in the nursery. They have been collected from the time of the Dutch era until now. These collections were obtained from botanical explorations throughout the forests of Indonesia and through seed exchange with botanic gardens around the world. Several of the Bogor aroid collections represent ‘living types’, such as Scindapsus splendidus Alderw., Scindapsus mamilliferus Alderw. and Epipremnum falcifolium Engl. These have survived in the garden from the time of their collection up until the present day. There are many aroid collections in the Gardens that have potentialities not widely recognised. The aim of this study is to reveal the diversity of aroids species in the Bogor Botanic Gardens, their scientific value, their conservation status, and their potential as ornamental plants, medicinal plants and food. The methods of the research include direct observation in the garden and nursery collections, analysis of the Gardens’ long-term registration database, as well as herbarium studies in both the Herbarium Bogoriense and the Gardens’own herbarium. A total of 130 species of aroids belonging to 36 genera have been cultivated in the Bogor Botanic Gardens. It is estimated that the gardens has 29% of the total number of genera in the world (21 genera are native to Indonesia). The aroid collection consists of terrestrial plants, aquatic plants and climbing plants (61 species, 12 species and 57 species, respectively). Amorphophallus paeoniifolius has developed further as a food plant. Genera such as Aglaonema, Alocasia, Apoballis, Rhaphidophora and Scindapsus have long been used as ornamental plants. Futhermore, some Homalomena species can be extracted for essential oils, while Epipremnum pinnatum has application in the treatment of cancer. Descriptions of some endemic, rare and high value species are discussed in this paper.